The clinical outcome of skeletal anchorage in interceptive treatment (in growing patients) for class III malocclusion. Issue 8 (August 2018) - Meyns, J.; Brasil, D.M.; Mazzi-Chaves, J.F.; Politis, C.; Jacobs, R.
Abstract: A systematic review of the literature was performed regarding the clinical outcome (effectiveness) of bone anchorage devices in interceptive treatment for class III malocclusion. A search of Embase, PubMed and Web of Science databases yielded 285 papers. An additional two articles were retrieved through manual searching of the reference lists. After initial abstract selection, 32 potentially eligible articles were screened in detail, resulting in a final number of eight articles included in this review. Insufficient evidence was found regarding the effects of skeletal anchorage in interceptive class III treatment to support definitive conclusions on long-term skeletal effects and stability. In the short term, it seems that bone anchors can provide more skeletal effect with less dentoalveolar compensations and less unwanted vertical changes. This does not always exclude the use of a face mask. The use of miniscrews as skeletal anchorage device does not seem to provide more skeletal effect, although it could minimize the unwanted dental effects in the upper jaw. No information regarding the need for orthognathic surgery, orthodontic treatment time or patient compliance and complications was found in the selected articles.